2012
DOI: 10.3390/metabo2010077
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of LC-MS Data Preprocessing Methods on the Selection of Plasma Biomarkers in Fed vs. Fasted Rats

Abstract: The metabolic composition of plasma is affected by time passed since the last meal and by individual variation in metabolite clearance rates. Rat plasma in fed and fasted states was analyzed with liquid chromatography quadrupole-time-of-flight mass spectrometry (LC-QTOF) for an untargeted investigation of these metabolite patterns. The dataset was used to investigate the effect of data preprocessing on biomarker selection using three different softwares, MarkerLynxTM, MZmine, XCMS along with a customized prepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 40 publications
0
47
0
3
Order By: Relevance
“…However, there is no currently available standardized soware/website for MS data processing and analysis. Using different soware, the results will be very different, [153][154][155] which shows that data processing and analysis soware/ websites have a great inuence on data processing. Data processing is a vital part of metabolomics research and each soware/website has its own characteristics.…”
Section: Tools For Ms Results Analysismentioning
confidence: 99%
“…However, there is no currently available standardized soware/website for MS data processing and analysis. Using different soware, the results will be very different, [153][154][155] which shows that data processing and analysis soware/ websites have a great inuence on data processing. Data processing is a vital part of metabolomics research and each soware/website has its own characteristics.…”
Section: Tools For Ms Results Analysismentioning
confidence: 99%
“…The main issue is that these software packages do not provide the same results -neither qualitatively (the metabolites found identified with a retention time m/z pair) -nor quantitatively (the relative concentration found in the different samples) [30]. In a recent metabolomics study, several software packages were compared and the shared and unique metabolites were reported [31]. Adding correlation studies on top of such data would further validate the shared metabolites and how the different software packages can extract the same information, as visualized in Fig.…”
Section: Multivariate Challenges and Opportunitiesmentioning
confidence: 97%
“…It is therefore of utmost importance to assess the quality of the peak picking since it defines the features available for further analysis and it is a huge task to find the correct settings (Brodsky et al 2010). Gürdeniz et al compared the performance of different pre-processing tools, but concluded that the selection of appropriate settings is more important than which software to choose (Gürdeniz et al 2012). Coble and Fraga in a later study focused on the different free softwares and suggests the combination of output from these to achieve high coverage and robust data (Coble and Fraga 2014).…”
Section: Data Pre-processingmentioning
confidence: 97%